On Langevin Type of Fractional Time - Delay Differential Equations - Aydın, Mustafa (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2023)
The existence uniqueness of solutions of the impulsive delayed fractional differential equations(IDFDEs) was proved. The Ulam-Hyers stability of IDFDEs was demonstrated. The controllability of IDFDEs was shown via iterative learning control technique. In the sequel, the neutral fractional multi-delayed differential equations(NFMDDEs) was introduced. The existence and uniqueness of NFMDDEs was investigated in addition to its stability, and relative controllability of NFMDDEs was proved by means of fixed point technique. Lastly, new fractional integral and derivatives, i.e. φ-generalized Riemann Liouville k-fractional integral, φ-generalized Riemann Liouville k-fractional derivative, φ-generalized Caputo k-fractional derivative were defined and some fundamental features were discussed to build theory’s basement.

ÖZ: ˙Impulsif ve gecikmeli kesirli bir diferansiyel denklemin çözümünün var ve tek oldugu˘ ispatlandı. Bu kesirli diferansiyel denklemin Ulam-Hyers anlamında kararlı oldugu˘ gösterildi. Yinelemeli ögrenme kontrol edilebilirlik tekni ˘ gi yardımıyla da bu ˘ denklemin kontrol edilebilecegi gösterildi. Hemen akabinde, çok gecikmeli nötr ve ˘ kesirli diferansiyel denklemi tanıtıldı. Bu kesirli diferansiyel denklemin kararlılıgına ˘ ilaveten sistemin çözümünün var ve tek oldugu ara¸stırıldı ve sabit nok teoremleri ˘ teknigi aracılı ˘ gıyla bu kesirli diferansiyel denklemin nisbi kontrol edilebilece ˘ gi ispat ˘ edildi. Son olarak, φ-genelle¸stirilmi¸s Riemann Liouville k-kesirli integrali, φ-genelle¸stirilmi¸s Riemann Liouville k-kesirli türevi, φ-genelle¸stirilmi¸s Caputo k-kesirli türevi olmak üzere yeni kesirli integral ve türevleri tanımlandı ve teorinin temelini in¸sa etmek için bazı temel özellikler tartı¸sıldı.
Doctor of Philosophy in Mathematics. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Mathematics, 2023. Supervisor: Prof. Dr. Nazım Mahmudov
Keywords: Thesis Tez